2012
DOI: 10.2174/2211556011201040301
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Under the Influence: Transcriptional Profiling of Ethanol in the Brain

Abstract: Sensitivity to ethanol intoxication, propensity to drink ethanol and vulnerability to develop alcoholism are all influenced by genetic factors. Conversely, exposure to ethanol or subsequent withdrawal produce gene expression changes, which, in combination with environmental variables, may participate in the emergence of compulsive drinking and relapse. The present review offers an integrated perspective on brain gene expression profiling in rodent models of predisposition to differential ethanol sensitivity or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 80 publications
(176 reference statements)
3
35
0
Order By: Relevance
“…We have recently shown up-regulation of several subunit mRNAs of ionotropic glutamate (GluA2 and GluA3, GluK2, GluK3 and GluK5, GluN1, GluN2A, GluN2C, GluN2D and GluN3A) and GABA-A receptors (α1, α5, β1, and γ1) in the hippocampal dentate gyrus, up-regulation of GluN3A but down-regulation of GABA-A β2 and δ in the orbitofrontal cortex, and no difference in subunit expression in the dorsolateral prefrontal cortex of human alcoholics as compared to control subjects (Jin et al, 2012, 2014). Importantly, our studies and other gene expression studies on human post-mortem brain (Flatscher-Bader et al, 2006; Contet, 2012; Ponomarev et al, 2012), show that changes in gene expression pattern of the ionotropic glutamate and GABA-A receptors subunits induced by chronic alcohol intake greatly vary between brain regions.…”
Section: Discussionsupporting
confidence: 64%
“…We have recently shown up-regulation of several subunit mRNAs of ionotropic glutamate (GluA2 and GluA3, GluK2, GluK3 and GluK5, GluN1, GluN2A, GluN2C, GluN2D and GluN3A) and GABA-A receptors (α1, α5, β1, and γ1) in the hippocampal dentate gyrus, up-regulation of GluN3A but down-regulation of GABA-A β2 and δ in the orbitofrontal cortex, and no difference in subunit expression in the dorsolateral prefrontal cortex of human alcoholics as compared to control subjects (Jin et al, 2012, 2014). Importantly, our studies and other gene expression studies on human post-mortem brain (Flatscher-Bader et al, 2006; Contet, 2012; Ponomarev et al, 2012), show that changes in gene expression pattern of the ionotropic glutamate and GABA-A receptors subunits induced by chronic alcohol intake greatly vary between brain regions.…”
Section: Discussionsupporting
confidence: 64%
“…Dlg2 encodes for post-synaptic density protein 93 (PSD-93), Gatad2b encodes for transcriptional repressor p66-beta, Pcdhac2 encodes for protocadherin αc2, Tnks encodes for Tankyrase-1, Usp29 encodes for ubiquitin specific protease 29 and Usp9x encodes for ubiquitin specific protease 9, X-linked. That two ubiquitin-related genes are in this group cannot be unexpected, given the long standing observations that ubiquitination is associated with chronic ethanol exposure in both animals and humans (see Sokolov et al, 2003; Liu et al, 2006; Contet, 2012; Melendez et al, 2012; Widagdo et al, 2017). Our data link ubiquitination to risk for excessive consumption.…”
Section: Discussionmentioning
confidence: 97%
“…Contet (2012) surveyed the existing literature and noted that multiple functional categories were associated with a “predisposition” to excessive ethanol consumption and in most cases each of the categories have been supported by multiple publications (see Table 2 in Contet, 2012). Some regional specificity for each of the functional categories was also noted; however, the regional differences in gene expression were generally larger than those associated with selection for preference or binge drinking (Kimpel et al, 2007; Mulligan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for alcohol effects on nucleic acids structure, functions and metabolisms, it was shown that ethanol induced a complex pattern of hormonal responses in individual rats causing multiple changes in genes transcription processes [9]. Exposure to ethanol or subsequent withdrawal produced gene expression changes [10].…”
Section: Introductionmentioning
confidence: 99%